“The Negro Speaks of Rivers”ii An African Centered Historical Study of the Selfethnic Liberatory Adult Education Nature and Goals of the Poetry of Langston Hughes: the Impact on Adult Education - Sarah E. Howard (Adult Education Research Conference, 2010)
The purposes of this historical study were to document the Selfethnic liberatory adult education nature and goals of selected poetry of Langston Hughes published from 1921 to 1933; and to document the impact this poetry had on the field of adult education.